An analysis of latent heat thermal energy storage in a hexagonal triplex-tube unit with curve shape fin and CNTs. (August 2022) - Alizadeh, M.; Haq, R.U.; Hamid, M.; Nguyen, V.B.; Truong, T.H.; Ganji, D.D.; Tian, Z.F.
Abstract: In this article, latent heat thermal energy storage (LHTES) is analyzed for nano phase change material enclosed in a hexagonal triplex-tube with solidification acceleration. Optimized curve shape fins are adjusted inside the tube. The shape of the structure is a hexagonal annular. Therefore, both inner hexagonal walls are cold. Corresponding to six vertices of the hexagonal shaped tube, parallel but symmetrically curved fins are adjusted to every corner. Nanoparticles Enhanced Phase Change Material (NEPCM) is filled inside the annulus, and the mathematical model is constructed based upon the system of nonlinear partial differential equations through the heat equation. Single wall carbon nanotubes (SWCNT) and Copper driven through liquid phase and solid phase within the entire duct. Galerkin Finite Element Method (GFEM) is employed to model the solidification procedure. The smaller symmetric fins achieving an angle of 10 o ≤ β 1 ≤ 45 o and the larger symmetric fins making an angle of 10 o ≤ β 2 ≤ 45 o with the vertical rod. However, the length of rod is 10 m m ≤ L ≤ 20 m m . It is found that the optimized curve shape fin penetrate the intensity of thermal storage into the Phase change materials (PCM) and the shape of the fin prevents the phase trade manner from final unsolidified PCM near the outer shell, in which the phase alternate front passes the top of the fins. It is further analyzed that at the mean position of the triplex tube, the solidification process is minimum due to the high thermal performance of nanoparticle volume fraction and time perfection. Graphical abstract: These figures configure the variation of solid fraction and solidification time behavior with phase change material. Image 1